Negotiating Closed Doors and Constraining Deadlines: The Potential of Visual Ethnography to Effectually Explore Private and Public Spaces of Motherhood and Parenting. (December 2018) - Mannay, Dawn; Creaghan, Jordon; Gallagher, Dunla; Marzella, Ruby; Mason, Sherelle; Morgan, Melanie; Grant, Aimee
Pregnancy and motherhood are increasingly subjected to surveillance by medical professionals, the media, and the general public, and discourses of ideal parenting are propagated alongside an admonishment of the perceived "failing" maternal subject. However, despite this scrutiny, the mundane activities of parenting are often impervious to ethnographic forms of inquiry. Challenges for ethnographic researchers include the restrictions of becoming immersed in the private space of the home where parenting occurs and an institutional structure that discourages exploratory and long-term fieldwork. This paper draws on four studies, involving thirty-four participants, that explored their journeys into the space of parenthood and their everyday experiences. The studies all employed forms of visual ethnography, including artifacts, photo elicitation, timelines, collage, and sandboxing. The paper argues that visual methodologies can enable access to unseen aspects of parenting and engender forms of temporal extension, which can help researchers to disrupt the restrictions of tightly time bounded projects.